ANALISIS PELAKSANAAN SUPERVISI AKADEMIK OLEH KEPALA SEKOLAH DI SEKOLAH DASAR - Azzahra, Aulia; Sri Marmoah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Academic supervision is a series of activities organized by the school principal and a team of supervisors to assist teachers in developing their ability to manage the learning process so that learning objectives are achieved. The objectives of academic supervision are to enhance teachers’ professionalism and competence, foster and strengthen motivation in carrying out teaching duties, improve the quality of the learning process and outcomes, and help align educational programs with the needs and conditions of the environment. This study aims to examine the implementation of academic supervision by school principals so that in the future, both principals and teachers can implement supervision more effectively and minimize obstacles. This study employs a literature review approach based on 19 national articles. The results indicate that, overall, the implementation of academic supervision in several Indonesian elementary schools is quite good in accordance with existing standards. However, numerous obstacles were also identified in the implementation of academic supervision, such as teachers feeling burdened by supervision, schedules sometimes conflicting with the principal’s events, incomplete teacher documentation, teachers’ lack of preparedness for supervision, the absence of a standardized academic supervision format, the principal’s insufficient knowledge and understanding of academic supervision, time constraints, and the principal being overly busy. Therefore, an appropriate implementation strategy is necessary to ensure that academic supervision is carried out effectively and efficiently.